Respuesta :

Answer:

x = -10/7

Step-by-step explanation:

Assume that you meant (2/4)x - (1/5)x = x - 1.  The parentheses are important for clarity.  

Start the solution by combining the x terms.  Note that the LCD here is 20, and that the problem thus becomes

                                        (10/20)x - (4/20)x = x - 1

This simplifies to                     (6/20)x = x - 1, or

                                                  (3/10)x = x - 1

Note that 'x' = '10/10x', and so    (3/10)x = (10/10)x - 1, or

                                                       -1         =    (7/10)x

Multiplying both sides by 10, we get 7x = -10, and therefore x = -10/7